Producing figurative expression theoretical, experimental and practical perspectives - Barnden, John; Gargett, Andrew D. (Figurative thought and language ;, 2020)
"This collection contains a selection of recent work on people's production of figurative language (metaphoric, ironic, metonymic, hyperbolic, ...) and similarly of figurative expression in visual media and artefact design. The articles illuminate issues such as why and under what circumstances people produce figurative expression and how it is moulded by their aims. By focusing on production, the intention is to help stimulate more academic research on it and redress historically lower levels of published work on generation than on understanding of figurative expression. The contributions stretch across various academic disciplines-mainly psychology, cognitive linguistics and applied linguistics, but with a representation also of philosophy and artificial intelligence-and across different types of endeavour-theoretical investigation and model building, experimental studies, and applications focussed work (for instance, figurative expression in product design and online support groups). There is also a wide-ranging introductory chapter that touches on areas outside the scope of the contributed articles and discusses difficult issues such as a complex interplay of production and understanding"--